Edukasi Puasa Pre Operatif dalam Upaya Peningkatan Pengetahuan Pasien General Anestesi - Habibillah, Sultan Dafa; Jerau, Emiliani Elsi; Setyawati , Martyarini Budi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Preoperative fasting is an important procedure before surgery to prevent aspiration and anesthesia-related complications. However, many patients only know the rule of fasting from the night before surgery without understanding the medical reasons behind it. Lack of education may reduce compliance and increase the risk of complications. This Community Service activity aimed to assess participants’ knowledge and improve their understanding of the importance of preoperative fasting. The method used was health education through individual lectures for patients in the wards of Purwokerto Islamic Hospital, involving 20 participants from various backgrounds. Knowledge levels were measured using pre-test and post-test questionnaires. Results showed that before the education, 12 participants (60%) had low knowledge, 6 participants (30%) had moderate knowledge, and 2 participants (10%) had good knowledge. After the education, there was a significant improvement: 12 participants (60%) were in the good category, 6 participants (30%) in the moderate category, and only 2 participants (10%) in the low category. In conclusion, the lecture method proved effective in increasing patients’ knowledge about preoperative fasting as it allows two-way communication, structured information delivery, and adaptation to patients’ conditions, making the information easier to understand.